Pericytes are involved in the pathogenesis of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy. Issue 6 (7th October 2015) - Ghosh, Mitrajit; Balbi, Matilde; Hellal, Farida; Dichgans, Martin; Lindauer, Ute; Plesnila, Nikolaus
Abstract : Objective: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), the most common inherited small‐vessel disease, is associated with vascular aggregation of mutant Notch3 protein, dysfunction of cerebral vessels, and dementia. Pericytes, perivascular cells involved in microvascular function, express Notch3. Therefore, we hypothesize that these cells may play a role in the pathogenesis of CADASIL. Methods: Two‐, 7‐, and 12‐month‐old CADASIL mutant mice (TgNotch3 R169C ) and wild‐type controls were examined regarding Notch3 aggregation in pericytes, the coverage of cerebral vessels by pericytes, pericyte numbers, capillary density, blood–brain barrier (BBB) integrity, astrocytic end‐feet, and the expression of astrocytic gap junction and endothelial adherens junction protein using immunostaining and Western blot analysis. In addition, we examined cerebrovascular CO2 reactivity using laser Doppler fluxmetry and in vivo microscopy. Results: With increasing age, mutated Notch3 aggregated around pericytes and smooth muscle cells. Notch3 aggregation caused significant reduction of pericyte number and coverage of capillaries by pericyte processes ( p < 0.01). These changes were associated with detachment of astrocytic end‐feet from cerebral microvessels, leakage of plasma proteins, reduction in expression of endothelial adherens junction protein, and reduced microvascular reactivity to CO2 . Smooth muscle cells were not affected by Notch3 accumulation. Interpretation: Our results show that pericytes are the first cells affected by Notch3 aggregation in CADASIL mice. Pericyte pathology causes opening of the BBB and microvascular dysfunction. Therefore, protecting pericytes may represent a novel therapeutic strategy for vascular dementia. Ann Neurol 2015;78:887–900